1996
DOI: 10.1007/bf01254478
|View full text |Cite
|
Sign up to set email alerts
|

A non-negative fast multiplicative algorithm in 3D scatter-compensated SPET reconstruction

Abstract: Single-photon emission tomographic (SPET) reconstruction can be improved, especially for noisy images, by using the iterative expectation-maximization of the maximum-likelihood (EM-ML) algorithm. Its application to clinical routine is, however, hampered by the high number of iterations necessary to achieve acceptable results. Therefore various methods have been developed to accelerate the EM-ML algorithm. In this paper a new accelerated EM-ML-like multiplicative algorithm is proposed for SPET reconstruction. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Because of the proximity of high liver activity, we found that iterative reconstruction [37] provided better results than standard filtered back projection. Underdetection of occult AS during laparoscopic splenectomy was the cause of these residual spots in at least one of our patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Because of the proximity of high liver activity, we found that iterative reconstruction [37] provided better results than standard filtered back projection. Underdetection of occult AS during laparoscopic splenectomy was the cause of these residual spots in at least one of our patients.…”
Section: Discussionmentioning
confidence: 91%
“…Reconstruction was performed by means of an iterative Љfalse likelihood algorithmЉ [37] with scatter correction [36]. This algorithm is an accelerated version of the Љexpectation of maximum likelihoodЉ (EML) method, which preserves the pixel positivity inside the body and null activity outside.…”
Section: Preoperative Localizationmentioning
confidence: 99%
“…Imaging data were recorded using a micro single photon emission computed tomography (SPECT) instrument capable of high-level spatial resolution to ϳ1.7 mm (18). For each study, 60 projections were acquired at 6°intervals, and the images were reconstructed using an implementation of the EM-ML algorithm (19). After completion of the SPECT study, animals were placed in the high-resolution (to 50 m) micro-computed tomography (CT) apparatus, and 180 projections were collected.…”
Section: Radioimaging Studiesmentioning
confidence: 99%
“…MRP generates quantitatively stable solutions with respect to the number of iterations [1]. This is a very interesting property since it is well known that the increase in the iteration number tends to generate less quantitatively accurate solutions in the MLEM process [1][2][3]. Among the major advantage of MRP, two are worth mentionning.…”
Section: Introductionmentioning
confidence: 98%
“…For application in clinical routine, the use of an accelerating procedure is highly desirable. This is for example particularly true in low count density regions where a large number of iterations is required [3]. An accelerating procedure that would limit the noise generated by the numerous iterations would therefore be very appreciable.…”
Section: Introductionmentioning
confidence: 99%